Class Teacher Strategies in Facilitating the Learning Needs of Special Needs Students at MIN 9 Banda Aceh City - Alisha Zahara Saadiya; Wanty Khaira (International Journal of Technology and Education Research, 2025)
This study aims to determine the strategies implemented by class teachers who also serve as guidance and counseling teachers at MIN 9 Banda Aceh City in facilitating learning needs in the category of students with special needs. By looking at the strategies that have been implemented by class teachers as guidance and counseling teachers, new discoveries will be found in providing needs that are adjusted to the category of students with special needs. This study uses a qualitative approach, by combining data obtained through field observations, detailed interviews with class teachers as guidance and counseling teachers, homeroom teachers, Head of the Inclusive Education Service Team and analysis of related documents such as inclusive student profiles. The results of the study explain that the strategies implemented by class teachers as guidance and counseling teachers include game approaches, individual, and communication built with parents of students. The game approach carried out by teachers such as; inviting students to play while singing and teachers actively accompany students with special needs. The individual approach carried out by teachers, students are accompanied to study lessons they do not understand and help students who experience obstacles in the learning process. In addition, the role of parents is very important in educating and encouraging their children to achieve success in the learning process. However, despite the obstacles experienced in implementing this strategy, teachers must be able to adapt to the needs of each student with special needs